What’s in a Name? Limits in Parmenides’ Sequentialism - Marco Guerrieri (Peitho)
In this paper, the problem of compatibility between the two parts of the poem by Parmenides of Elea is addressed. This is done on the basis of a number of fragments from the poem – B 8, 9, 12, 16 and others – and a study of their ancient testimonia. In this way, the Parmenidean conception of the world and of human perceptive and gnoseological activity within it is reconstructed. Furthermore, starting from textual clues that show a certain need to go beyond this view of the world, an attempt has been made to argue how τὸ ἐόν can be understood as the All, i.e. as the universe, but seen in its unity. In order to do so, a tempative answer was proposed, using the philosophical category of limit, to recent aporias raised by interpreters.